Crystal structure of N-(2-methylphenyl)(propan-2-yloxy)carbothioamide, C11H15NOS - Yeo, Chien Ing *; Tiekink, Edward R. T. * (de Gruyter, 2019)
The title crystal structure is shown in the figure. Tables 1 and 2 contain details on crystal structure and measurement conditions and a list of the atoms including atomic coordinates and displacement parameters